Condições físico-hídricas de solos mato-grossenses e sua relação com a produtividade de soja : da pesquisa à transposição didática - Bocuti, Edwaldo Dias (2020)
Research focused on soybean cultivation in Mato Grosso has required a better understanding of two aspects of the agricultural production process of this crop: the first one consists on investigating the factors that lead to various crop areas to stagnant productivity, and the second one is that soils of the same class, subjected to similar annual precipitation regime and properly fertilized, have shown very different grain yields. Research on indicators and soil quality indicators can contribute to explain the aspects mentioned above and provide opportunities for the spread of knowledge at different levels of schooling. Given the above, the objective of this study was to diagnose the physical and physical-hydric condition of soils in Mato Grosso, to analyze the reflection of such conditions in soybean yields and to promote the transposition of technical and scientific information into school knowledge. For that, some areas of soybean production located in Mato Grosso were selected, in which, preserved, semipreserved and deformed soil samples were collected to analyze a set of physical and physical-hydric attributes, which were subjected to the Kruskal-Wallis test at 5% probability. Based on soils attributes and the analysis of their main components, physical soil quality indexes were established for soybean production areas. In addition to this study, the scientific knowledge obtained in the research on the physical quality of soils was transposed into the form of objects of school knowledge and organized in the form of didactic material. Regarding to the agronomic results of this research, it was found that soils with clay content between 137.26 to 521.97 g kg-1 presented soybean productivity potential from 3,891.43 to 4,080.00 kg ha-1 . The implantation of soybean crops in soils with an average clay content from 6 to 12% had productivity according to the management technique and production technologies. Soils with average hydraulic conductivity between 63 and 127 mm h-1 compromised the storage and availability of water to the crop and converged to lower soybean yields. The index values of the physical soil quality in the study areas ranged from 1.73 to 2.48 and among the study areas, eight were classified as having high physical soil quality, eight as medium quality and five as low quality. It was verified that the physical quality of the soils cultivated with soybean is mainly related to inherent characteristics of the soil aggregates. From the perspective of the results in the scope of basic education, it was observed that through the didactic transposition, it was possible to elaborate a pedagogical notebook that will contribute to the progression of the students' learning about the object of knowledge “soil quality”, which is a relevant for a great number of students in the state. Through this study, it was possible to establish a joint between society, sustainability agricultural and university.